2021
DOI: 10.1007/s00330-021-08320-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning–assisted prostate cancer detection on bi-parametric MRI: minimum training data size requirements and effect of prior knowledge

Abstract: Objectives To assess Prostate Imaging Reporting and Data System (PI-RADS)–trained deep learning (DL) algorithm performance and to investigate the effect of data size and prior knowledge on the detection of clinically significant prostate cancer (csPCa) in biopsy-naïve men with a suspicion of PCa. Methods Multi-institution data included 2734 consecutive biopsy-naïve men with elevated PSA levels (≥ 3 ng/mL) that underwent multi-parametric MRI (mpMRI). mpMRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…This method can be applied on both 2D and 3D T2w MRI sequences. The obtained results not only are similar to the results from the state of the art but are also coherent with the results obtained by radiologists and globally preserving zonal locations and sectorial positions of the lesions, making our method suitable as a first step tool for an automated system dedicated to diagnosis and grading of PCa, as done by Hosseinzadeh et al 70 or by Mehta et al 71…”
Section: Discussionsupporting
confidence: 88%
“…This method can be applied on both 2D and 3D T2w MRI sequences. The obtained results not only are similar to the results from the state of the art but are also coherent with the results obtained by radiologists and globally preserving zonal locations and sectorial positions of the lesions, making our method suitable as a first step tool for an automated system dedicated to diagnosis and grading of PCa, as done by Hosseinzadeh et al 70 or by Mehta et al 71…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have shown that deep learning strategies can achieve better outcomes than simpler systems that make use of pathology samples [ 29 ]. There are other examples of algorithms based on artificial intelligence and machine learning in PCa that could be an excellent addition to our work [ 30 , 31 , 32 ]. Finally, considering the difficulties to segment the prostate gland regions, a solution based on AI was proposed by Bardis et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expert panel and studies suggest a minimum of 100 training cases before obtaining an AUC on par with more experimented readers [ 70 , 71 ]. However, training requirements may be drastically modified by the introduction of new machine learning algorithms to assist prostate MRI analysis [ 72 , 73 ].…”
Section: Diffusion-weighted Prostate Imagingmentioning
confidence: 99%